2020
DOI: 10.1099/acmi.0.000140
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the complete genomes of carbapenem-resistant Acinetobacter baumannii harbouring bla OXA-23, bla OXA-420 and bla NDM-1 genes using a hybrid-assembly approach

Abstract: Carbapenem resistance in Acinetobacter baumannii is due to bla OXA-23, which is endemic in India. Recently, the sporadic presence of bla OXA-58 as well as the occurrence of dual carbapenemases were observed. The mobility as well as the dissemination of these resistance genes were mainly mediated by various mobile genetic elements. The present study was aimed at characterizing the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
4
11
0
Order By: Relevance
“…This genetic organization is similar to that of Tn125like transposon previously reported by Bonnin et al (2013). BLAST analysis of the contigs harboring bla NDM-1 showed highest similarity to the chromosome of A. baumannii strain ACN21 (GenBank accession: CP038644.1; Vijayakumar et al, 2020).…”
Section: Genetic Context Of Resistance Genessupporting
confidence: 82%
See 1 more Smart Citation
“…This genetic organization is similar to that of Tn125like transposon previously reported by Bonnin et al (2013). BLAST analysis of the contigs harboring bla NDM-1 showed highest similarity to the chromosome of A. baumannii strain ACN21 (GenBank accession: CP038644.1; Vijayakumar et al, 2020).…”
Section: Genetic Context Of Resistance Genessupporting
confidence: 82%
“…This was previously documented by Bonnin et al (2013) who failed to identify a downstream second copy of ISAba125 by PCR and suggested loss of functionality of this truncated transposon (ΔTn125). WGS of bla NDM -positive isolates by a later study (Vijayakumar et al, 2020) uncovered the existence of a second copy of ISAba125 downstream to the ISAba14-interrupted transposon. Interestingly, analysis of the upstream region to the truncated transposon revealed the existence of the amikacin resistance gene AphA6 preceded by another copy of ISAba14 in ST85 Pas Intrinsic to all A. baumannii, cephalosporin resistance is mediated by ADC (formerly known as bla AmpC ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 110 , 111 ], Shigella spp. [ 104 , 112 , 113 ], Pseudomonas spp. [ 102 , 105 , 108 , 109 ], and Acinetobacter spp.…”
Section: A Snapshot Of Amr Surveillance Programs and The Epidemiologymentioning
confidence: 99%
“…The main genetic structures of pRYU24, nucleotides 1-38 198 containing armA and nucleotides 46 459-53 186 containing bla OXA-420 , were 99.82 and 99.78 % similar to those of nucleotides 1-38 188 and 48 634-55 368, respectively, of the ACN21 plasmid present in an isolate of A. baumannii obtained in 2018 in India (Fig. 3) [33]. Another genetic structure of pRYU24, nucleotides 57 553-66 524 containing bla NDM-1 , had 99.77% similarity to nucleotides 4043-13 029 of the pNDM-GJ02 plasmid present in an isolate of Acinetobacter towneri strain G295 obtained in 2011 in PR China [34].…”
Section: Resultsmentioning
confidence: 71%